2020
DOI: 10.1063/1.5129511
|View full text |Cite
|
Sign up to set email alerts
|

Modulated wall motion approach for augmenting slug flow heat transfer between two micro-parallel plates

Abstract: Liquid–liquid slug flow heat transfer in microchannels has been an interesting topic of research to many researchers. However, the heat transfer studies available in the existing literature deal with stationary walls of the microchannels. In the present work, a modulated motion is prescribed to the walls of the channel in the transverse direction during oil–water slug flow between micro-parallel plates. The influence of frequency and amplification factor of the modulated wall motion as well as capillary number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The simulation results showed that the backflow region shrank with increasing liquid flow rate and bubble velocity and a significant pressure drop occurred in film flow when passing through the minimum film area. Vivekanand et al [32] carried out numerical simulations of the effects of modulated wall motion on slug flow and heat transfer and showed that it significantly improved heat transfer. Most of those numerical simulations, which were based on their own models incorporating micro region contribution to heat transfer, have supported an important role of microlayer played to boiling heat transfer [28] , [33] .…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results showed that the backflow region shrank with increasing liquid flow rate and bubble velocity and a significant pressure drop occurred in film flow when passing through the minimum film area. Vivekanand et al [32] carried out numerical simulations of the effects of modulated wall motion on slug flow and heat transfer and showed that it significantly improved heat transfer. Most of those numerical simulations, which were based on their own models incorporating micro region contribution to heat transfer, have supported an important role of microlayer played to boiling heat transfer [28] , [33] .…”
Section: Introductionmentioning
confidence: 99%
“…Results revealed that the heat transfer significantly increases with modulated wall temperature over unmodulated wall temperature boundary condition. Another study by Vivekanand and Raju (2020) examined the thermal performance of Taylor flow under modulated wall motion. They observed 23% improvement in heat transfer with modulated wall motion compared to unmodulated wall motion.…”
Section: Introductionmentioning
confidence: 99%